2014
DOI: 10.1111/cbdd.12489
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Biological Evaluation, and Molecular Docking of Novel Benzopyran and Phenylpyrazole Derivatives as Akt Inhibitors

Abstract: By inspiration of good Akt1 inhibitory and cytotoxic activity of our previously screened hits 1 and 2, a series of novel benzopyrans 3a-c, 4 and phenylpyrazoles 5a-c, 6a-b, and 7 were designed, synthesized, and biologically evaluated for their in vitro Akt1 inhibitory and cytotoxic activity. The results revealed that all of these compounds showed moderate-to-excellent antiproliferative effects against the tested cancer cell lines (i.e. HL-60, OVCAR, PC-3, and HepG2). Among them, compounds 3a and 3c exhibited p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…On the contrary, 65 was totally inactive in the same cell lines. Aminomethyl residues were introduced on the C-6 site of quercetin by reaction with amines and formaldehyde providing the benzopyran derivatives 67 – 69 , which were biologically essayed for in vitro cytotoxicity or RAC-alpha serine/threonine-protein kinase Akt1 inhibitory activity [ 70 ]. In detail, the cytotoxic action of 67 – 69 was tested against HL-60, OVCAR-8, PC-3, and HepG2 human cancer cell lines using the known Akt inhibitor HT-89 as a positive control [ 71 ].…”
Section: Synthesis and Anticancer-related Activities Of Quercetin mentioning
confidence: 99%
“…On the contrary, 65 was totally inactive in the same cell lines. Aminomethyl residues were introduced on the C-6 site of quercetin by reaction with amines and formaldehyde providing the benzopyran derivatives 67 – 69 , which were biologically essayed for in vitro cytotoxicity or RAC-alpha serine/threonine-protein kinase Akt1 inhibitory activity [ 70 ]. In detail, the cytotoxic action of 67 – 69 was tested against HL-60, OVCAR-8, PC-3, and HepG2 human cancer cell lines using the known Akt inhibitor HT-89 as a positive control [ 71 ].…”
Section: Synthesis and Anticancer-related Activities Of Quercetin mentioning
confidence: 99%
“…On the basis of multiple previous research projects, most of the ATP-competitive Akt inhibitors were found to share common pharmacophore characteristics, including a hinge-binding group, a basic center, and a hydrophobic group. These three pharmacophores generate a “Y” shape through a linkage.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Conformational restriction is one of the most effective methodologies for drug design, since it can help improve the PK profiles of compounds and stabilize a favorable binding pattern to improve the binding affinities or kinase isoform selectivity. , This strategy has been widely applied in drug discovery. , In fact, some Food and Drug Administration-approved drugs were discovered and developed by using conformational restriction, such as Dolutegravir . In our previous study, the discovery of a series of 4,4-disubstituted piperidine derivatives featuring more restricted conformations in contrast to GSK-795 were successfully achieved, which proved that conformational restriction strategy could be used for discovery of new Akt inhibitors with novel skeletons. As a continuation of this earlier work, herein, the structural modifications of 3,4-disubstituted piperidine derivatives were reported, which exhibit excellent potency and good PK profiles.…”
Section: Introductionmentioning
confidence: 99%
“…As proposed by the authors, computational studies suggested two main interactions between the flavonoid compound and AKT1: (i) the catechol moiety formed two hydrogen bonds with the residues Ala230 and Glu228, and (ii) the 5-hydroxyl group of the carboxylic oxygen of the chromanone ring interacted with the Lys179 residue. In an effort to enhance the inhibition activity of this chemical family, 17 was submitted to chemical optimization [ 31 ]. Based on docking and MD simulations, only derivative 18 was selected for further studies, as this compound was predicted to establish an additional hydrogen bond involving the 7-hydroxyl group and a π-π stacking interaction between one phenyl functionality and the Phe161 residue ( Figure 8 ).…”
Section: Atp-binding Sitementioning
confidence: 99%